Minat Dan Peningkatan Kemampuan Berpikir Analitik Siswa Melalui Implementasi Media Video Tracker Materi Momentum - Mardiyah, Sofiatun; Subali, Bambang (Unnes Physics Education Journal, 2024)
The issue with the momentum material is that some students still rely on memorization to understand the concept of momentum, making it challenging to apply the concept to different conditions. This study aims to determine the impact of tracker videos on students’ analytical thinking and learning interest. The research use an experimental method with a Quasi-Experimental design, and the technique used was the One Group Pretest-Posttest. The sample for this study was class XI MIPA 1 at MA Mathalibul Huda Mlonggo in Jepara. Data collection techniques included pretests-posttests and questionnaires. Based on the research findings, the N-Gain test scored 0.9, which falls into the high category. These results indicate that tracker videos significantly influence students’ analytical thinking. The questionnaire results showed a very high positive level at 26%, with the participation of 7 students, a high positive level at 57%, and a moderate positive level at 17%. The conclusion of this study is that tracker videos can significantly increase students’ learning interest.